2019
DOI: 10.4038/slja.v27i1.8364
|View full text |Cite
|
Sign up to set email alerts
|

Is knowledge and attitude on epidural analgesia during labour satisfactory among pregnant women attending antenatal clinics in Colombo District?

Abstract: Labour pain management is a major challenge in maternity care. Epidural analgesia provides safe and effective pain relief during labour. The objective was to assess the knowledge, attitudes and associated factors towards epidural analgesia during labour among pregnant women in Colombo region, Sri Lanka.This was a descriptive study conducted at two selected hospitals in Colombo Sri Lanka. The sample size was 260 and those below 18yrs were excluded. Participants were provided with a pretested questionnaire. Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Several studies performed in low-income countries, have identified significant barriers to the use of epidural analgesia for labour and delivery. These include costs, availability of specialised staff and material, awareness of existing labour pain management techniques and beliefs that labour pain is natural and good and should not be treated 24–26. In our study of women having migrated from low-income countries, participants from all ethnic groups were aware of the different management techniques for labour pain, of their risks and benefits and had some level of knowledge of the epidural technique itself.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies performed in low-income countries, have identified significant barriers to the use of epidural analgesia for labour and delivery. These include costs, availability of specialised staff and material, awareness of existing labour pain management techniques and beliefs that labour pain is natural and good and should not be treated 24–26. In our study of women having migrated from low-income countries, participants from all ethnic groups were aware of the different management techniques for labour pain, of their risks and benefits and had some level of knowledge of the epidural technique itself.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study suggest that a lack of sufficient knowledge to make informed decisions is the main reason for the negative attitude. Studies have concluded that the lack of knowledge and women's pride in enduring labor pains are the main reasons for their negative attitudes toward EA [ 11 ]. Nevertheless, only 36% of women considered ordering EA in their next delivery, whereas the rest were either uncertain or do not consider it, which is almost the same attitude as that exhibited by women in the UAE.…”
Section: Discussionmentioning
confidence: 99%
“…These women's pride in enduring labor pains is the main reason for their negative attitudes toward EA. They primarily lack sufficient knowledge to make informed decisions [ 11 ]. Nonetheless, those who know about EA choose not to use it because of preconceived notions about pain relief during labor pains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Operational Definition Painless labor: Refers to using pain relieve methods during labor as non-pharmacological and pharmacological methods to help women cope with labor pain or relieve it. (28) , McCauley et al (2017) (29) , Mousa et al (2018) (30) and Delwatta et al (2019) (31) . It was used to assess nurses' attitudes regarding painless labor (non-pharmacological and pharmacological methods).…”
Section: Research Hypothesismentioning
confidence: 99%